Evaluation and Measurement of Health-Related Quality of Life for Individuals with Diabetes Mellitus by Health Utilities Index Mark 3 (HUI3) System - Frank Mo; Howard Morrison; Bernard C.K. Choi; Lianne Vardy (The Scientific World Journal)
The Health Utilities Index Mark 3 (HUI3) is an important indicator when measuring the health-related quality of life (HRQOL) and assessing the burden of disease, especially for chronic conditions such as diabetes mellitus (DM). The objectives of this study were to evaluate the scores of HRQOL for respondents with DM to examine associations between overall HUI3 scores and eight component attributes, and various sociodemographic and lifestyle attributes, and by doing so, provide information to improve the HRQOL of individuals with diabetes. The study was based on the Canadian National Population Survey (NPHS) longitudinal data, from 1994—1995 to 2002—2003. We evaluated overall HUI3 scores and eight attributes (vision, hearing, speech, ambulation, dexterity, emotion, cognition, and pain) between respondents with and without diabetes in relation to demographic characteristics (age, sex, lifestyle, and socioeconomic status using ANCOVA[analysis of covariance]). Awareness of diabetes appeared to affect the HRQOL of older age groups more so than younger age groups (p < 0.01). Diabetes also appeared to have a greater impact on males’ quality of life compared to females', and among individuals with single marital status and low socioeconomic status (p < 0.01). These findings add to what is known about cognitive representations and the self-regulation of diabetes as well as the relationships between cognitive representations of diabetes, HRQOL, and behavioral factors. In particular, results from this study suggest the need to address ways of reducing the burden of diabetes associated with health behaviours, and increasing the quality of life for the individuals with diabetes in Canada.